Differential Diagnosis of Urticarial Lesions - Matos, Ana Luísa; Figueiredo, Carolina; Gonçalo, Margarida (Frontiers in Allergy, 2022)
Urticaria is a common disease worldwide, with an important health burden. Although it is usually a straightforward diagnosis, many imitators may confound even the most experienced clinicians and some diagnoses cannot be missed. Urticaria is a mast cell-dependent disease, characterized by the presence of wheals, angioedema, or both in the absence of systemic symptoms. It can be acute or chronic. In the most common form of chronic urticaria, chronic spontaneous urticaria, wheals, angioedema or both occur without any specific triggers. Chronic recurrent urticarial syndromes can present with similar cutaneous lesions but most often additional atypical features are present, allowing the clinician to suspect a diagnosis other than urticaria. The authors propose an approach based on these atypical features, the presence or absence of systemic symptoms and on skin histopathology as well as some blood parameters.